Core-shell ZnO@TiO2 in water-based nanofluid for enhancing finned tube heat exchanger effectiveness - Yusuf Chandra; Syaharussajali; Muhammad Roy Ashiddiqi; Roes Arief Budiman; Suyanto; Ruri Agung Wahyuono (Case Studies in Thermal Engineering)
This study presents the thermal characteristics and stability of nanofluid dispersions using a core-shell composite of ZnO@TiO2 in a finned tube heat exchanger. Efforts to enhance the stability of ZnO nanoparticle dispersion were undertaken by depositing hydrophilic TiO2 nanoparticles with variations of three times the amount of deposition. The resulting 300–390 nm spherical aggregates of ZnO@TiO2 were then dissolved in water base fluid at low concentrations, ranging from 0.025 to 0.1 % by weight, as nanofluid in the finned tube heat exchanger. The results indicate that the thermal conductivity as well as the dispersion stability of ZnO@TiO2 nanofluid can be controlled by TiO2 layer thickness, where two layers of TiO2 increased dispersion stability by up to 10.3 times compared to ZnO nanofluid at a mass fraction of 0.1 %. Also, the thermal conductivity of ZnO nanofluid is enhanced from 1.15 W/m⋅K to 1.28 W/m⋅K. The LMTD-based heat transfer effectiveness of the heat exchanger shows that ZnO nanofluid provided the best effectiveness of 34.2 % at the highest mass fraction. Nonetheless, the ZnO@TiO2 core-shell nanofluid is considered optimum nanofluid condition since it is not only able to enhance the heat exchanger effectiveness up to 31.7 % but also to reduce the fouling factor in the heat exchanger due to the more stable dispersion in water base fluid.